Evaluating the Significance of Inspiratory Volumes and Capacity in Chronic Obstructive Pulmonary Disease - Maham Mazhar; Bushra Iftikhar; Jawaria Muhammad; Maria Muddassir; Ahmad Basirat; Tahir Maqbool; Faheem Hadi (Pakistan Journal of Medical Research)
Background: Smoking-induced Chronic obstructive pulmonary disease (COPD) is a chronic lung condition causing airflow obstruction and inflammation, leading to symptoms like breathlessness and fatigue. While expiratory issues are well-studied, the impact of inspiratory function on symptoms is less understood.